Not all roads can be taken: development induces anisotropic accessibility in morphospace. Issue 6 (11th September 2014) - Gerber, Sylvain
SUMMARY Morphospaces are quantitative representations of phenotype space that are widely used in studies of morphological evolution. Do current conceptualizations of morphospaces, however, appropriately reflect the evolutionary dynamics of organisms depicted in these spaces? Most empirical morphospace studies implicitly consider variability of biological forms as isotropic, but such a view appears inadequate when the properties of development mediating phenotypic changes are considered. Here, a trilobite case study is used to visualize the constraints imposed by development on the accessibility structure of morphospace. Variability in the resultant morphospace is strongly anisotropic and reveals discordances between the apparent range of possible phenotypes and their actual accessibility. Homoplasy, directionality, and asymmetry of evolutionary transitions appear as natural consequences of anisotropic variability and point out the limitation of morphological distance for evolutionary inference. Measures of distance in morphospace should be used with considerable caution and must be complemented with developmentally meaningful measures of evolutionary accessibility.